Hot water drenching of 'Hass' avocados for rot control - Terander, Emma (2007)
The occurrence of postharvest rots is a major issue for the New Zealand avocado industry, and much research is being carried out to find ways to control them. Since the use of many chemical fungicides and insecticides is being prohibited, there is a constant need for alternative, more environmentally friendly, methods to reduce disorders in fruit. One way to decrease the presence of rots in fruit is to maintain good orchard hygiene prior to harvest. There are also a number of ways to control rots, and their postharvest development. In recent years more attention has been turned towards heat treatments and their potential to reduce the development of rots. The aim of this project was to see whether the incidence of postharvest rots in avocados could be decreased by a hot water drench (HWD) of the fruit after harvest.